Energy, environmental and feasibility evaluation of tractor-mounted biomass gasifier for flame weeding. (March 2022) - Morselli, Nicoló; Puglia, Marco; Pedrazzi, Simone; Muscio, Alberto; Tartarini, Paolo; Allesina, Giulio
Abstract: Weed control is an agronomic technique that must be carried out on almost any cultivation, to prevent undesired weeds from competing with crops for nutrients, water, and light and reducing the annual yield. Nowadays, agriculture is experiencing a transition to both sustainable and organic approaches that is driving the increase in non-chemical treatments. Within this framework, thermal methods are gaining attention due to their higher working speed and effectiveness when compared to mechanical ones but thermal devices are still fueled with fossils leading to considerable greenhouse gas emissions. This work investigates the advantages of substituting liquefied petroleum gas (LPG) powered weeder with a portable gasification-based flame weeder fueled with woody biomass. Energy balance, carbon footprint and feasibility aspects are taken into account and the proposed solution is compared with the reference literature of LPG flame weeder. A flame weeder prototype is built starting from the gasification reactor of a commercial micro scale cogeneration unit. The gasifier is then fueled with A2-grade fir pellets and the syngas is burnt in a swirled flare designed for cross-flame weeding in woody crop rows. The biomass-fueled prototype is capable of a thermal flux directed towards the weeds of 208–247 kJ m −2 at a temperature that ranges from 850 to 980 °C. When compared to LPG systems applied to vineyards or orchards, the proposed solution reduces the fuel cost of the 72% and CO 2 emissions up to 118% considering the carbon-negative effect added by a 0.653 kg ha −1 of biochar production for each treatment. Results showed a specific fuel consumption of 52.2 kg ha −1 y −1 that can be self-sustained if vineyards prunings are used as fuel.